Gender Distribution of General Surgery Residents at the University of Puerto Rico - Cruz, Norma I.; Rivera, Fernando; Santiago, Elvis (Puerto Rico Health Sciences Journal, 2016)
Objective: To determine whether the number of women accepted to the University of Puerto Rico (UPR) general surgery residency program has increased in recent years. Methods: We examined the gender distribution of residents accepted in their first postgraduate year (PGY-1) by the UPR Surgery Department from 1958 to 2014. This information was obtained from the database of graduate residents, which collects information on gender, medical school from which they graduated, the years in which they were in the residency program, and, their specialty. We evaluated all the residents admitted to PGY-1 positions in surgery (1958–2014) and of those admitted to PGY-1 categorical general surgery positions (1983–2014). The study was IRB approved. Results: Since 1958 the number of female residents admitted as PGY-1s to the UPR Surgery Department has augmented, starting with 2% in the 1960s and rising to 36% in 2014. The percentage of categorical female residents was 11% in the 1983 to 1990 period, 14% in the 1991 to 2000 period, 18% in the 2001 to 2010 period, and 35% in the 2011 to 2014 period. Conclusion: We found an increase in the number of women admitted to the general surgery program over the last several years. However, despite this increase some degree of gender inequality remains in most surgery programs. Currently, 60% of undergraduate students and 50% of medical students are women, but only 36% of surgical residents are women. Future studies need to address the reasons for the small number of women in surgical programs.